Clinical utility of p16/Ki67 dual‐stain cytology for detection of cervical intraepithelial neoplasia grade two or worse in women with a transformation zone type 3: A cross‐sectional study. (22nd June 2022) - Gustafson, Line Winther; Tranberg, Mette; Christensen, Pia Nørgaard; Brøndum, Rikke; Wentzensen, Nicolas; Clarke, Megan A.; Andersen, Berit; Petersen, Lone Kjeld; Bor, Pinar; Hammer, Anne
Abstract: Objective: To evaluate the clinical utility of p16/Ki67 dual‐stain (DS) compared with cytology for detecting cervical intraepithelial lesion grade two or worse (CIN2+) in women with a transformation zone type 3 (TZ3). Design: Cross‐sectional study. Setting: Colposcopy clinics in Central Denmark Region. Population: Women aged 45 years or older referred for colposcopy because of an abnormal screening test. Methods: All women had a cervical sample collected for cytology and DS testing and underwent large‐loop excision of the transformation zone (LLETZ). Main outcome measure: Sensitivity, specificity and negative (NPV) and positive (PPV) predictive values of DS for CIN2+ detection were compared to those of cytology. Results: Of 166 women eligible, 93 (56.0%) were included in the final analysis. Median age was 68 years (interquartile range [IQR] 63.4–70.5 years). Most women were postmenopausal (95.7%) and referred based on a positive human papillomavirus screening test (86.0%). Fifty‐two women (55.9%) were DS‐positive, 29 (55.8%) of whom had CIN2+ detected. Twenty‐seven (29.0%) women had atypical squamous cells of undetermined significance or worse (ASC‐US+), and CIN2+ was detected in 21 women (77.8%). DS had a higher sensitivity (96.7% versus 70.0% p = 0.021) and NPV (97.6% versus 86.4%, p = 0.018) compared with cytology for CIN2+ detection. In contrast, the specificity (63.5% versus 90.5% p < 0.001) and PPV (55.8% versus 77.8%, p = 0.001) were lower for DS compared with cytology. Conclusions: Dual stain may be a valuable risk marker to guide clinical management of women with a TZ3. The superior NPV of DS suggests that a diagnostic excision may safely be avoided in DS‐negative women. Tweetable abstract: DS‐negative postmenopausal women with a TZ3 have a low risk of CIN2+ and may undergo follow up instead of LLETZ.